Influence of exogenous salicylic acid on phytochemical improvement and antioxidant activity in Cannabis sativa L. - Tebdoie, C.; Dewatthanawong, R.; Kongjinda, P.; Montri, N. (My University, 2024)
The impact of salicylic acid (SA) foliar spray at varied concentrations (0 and 1 M) and preharvest periods (24, 36, and 42 hours) on secondary metabolite in inflorescences of cannabis (Cannabis sativa L.) was investigated. Result was significantly differed in secondary compound composition. Application of 1 M SA at 24 hours preharvest increased total phenolics, total flavonoids, and total chlorophyll. Moreover, 1 M SA at 24 and 42 hours preharvest showed higher chlorophyll a and b contents than 1 M SA at 36 hours preharvest. While antioxidant activity was not significantly differed among 1 M SA treatments at different preharvest periods, it surpassed non-SA-treated plants. The total pigment was not significantly differed among SA treatments. 1 M SA spray reduced carotenoid content in cannabis inflorescences, with the highest carotenoid observed in non-SA treated plants.
Keywords: Cannabis; Plant hormone; Salicylic acid; Secondary compound